A critical analysis of the weak implementation causes on educational policies in Pakistan - Huma Akram; Yingxiu Yang (International Journal of Humanities and Innovation (IJHI), 2021)
The current technology era has provided education with a significant position to survive a society in this globalized world. However, Pakistan has made several efforts to raise the country’s education status but still unsuccessful in achieving the targets, for instance, struggling with low literacy. The current situation is mainly due to the poor implementation of educational policies. Therefore, a critical analysis of Pakistan education policies was done to understand the root causes of poor implementation and provide suggestions to resolve the weak areas. The study was followed by adopting a retrospective approach to review past literature, i.e., Education policies, research articles, project reports, and related literature. The study identified several barriers: excessive expectations, centralized targets, ambiguous objectives, political influence, inadequate funding and resources, lack of collaboration, scarcity of teachers’ professional development, and poor supervision. In conformity with the findings, some recommendations are also proposed. It is further claimed that local needs should be taken under consideration at the time of policy formulation to prevent policy failure. Targets of the educational plans should be formulated based on reality-oriented, thereby can be understood by everyone and may achieve easily. Furthermore, teachers should be facilitated with ongoing training programs to upgrade their knowledge and skills.